2020
DOI: 10.1108/ijhg-07-2019-0056
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Iranian non-governmental organizations in health policy-making; barriers and strategies for development

Abstract: PurposeThe effectiveness of non-governmental organization (NGO) participation in the healthcare sector has been demonstrated globally. The purpose of this paper is to investigate the status of Iranian NGOs’ contribution to health policy-making, the barriers to and strategies for developing their contribution.Design/methodology/approachIn this qualitative study, 25 participants were recruited from health-related NGOs in Tabriz, Iran. Semi-structured, in-depth qualitative interviews were conducted. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…A. [ 47 ] Bangladesh, 2017/ LMI Survey Self-reported ***** Providing services to mothers, infants and children, prevention and health care Khodayari-Zarnaq, R. [ 48 ] Iran, 2019/ UMI Qualitative study Semi-structured, in-depth qualitative interviews ***** Establishing and equipping hospitals, supplying medicine and treatment to the poor, financial support for orphans, providing loans to the poor, awareness, training vulnerable groups Maclure, R. [ 49 ] Burkina Faso, 1995/ LI Case study Interview *** Two NGOs providing first-aid clinics, maternities, and midwife lodgings for providing services for maternal health and child survival Manna, A. [ 50 ] India, 2019/ LMI Qualitative study Interview ** Using cell phones to communicate with cancer patients Mehta, P. [ 51 ] India, 2013/ LMI Cross-sectional Questionnaire *** Providing medical services for children with cancers Momoh, G. T. [ 52 ] Nigeria, 2015/ LMI Quasi experimental Semi-structured questionnaire/ in-depth interview ***** Strengthen the capacity of 12 NGOs in the field of support and policy related to the emphasis on reproductive health issues Mugisha F [ 53 ] Uganda, 2005/ LI Qualitative study Semi-structured individual interviews ***** Providing reproductive health services Mukherjee S [ 54 ] India, 2017/ LMI Descriptive study Case Studies, semi-structured interviews and unstructured observation/ literature review ***** Providing community participation Nguyen, N. [ 55 ] Low- and middle-income countries, 2014 Online survey …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. [ 47 ] Bangladesh, 2017/ LMI Survey Self-reported ***** Providing services to mothers, infants and children, prevention and health care Khodayari-Zarnaq, R. [ 48 ] Iran, 2019/ UMI Qualitative study Semi-structured, in-depth qualitative interviews ***** Establishing and equipping hospitals, supplying medicine and treatment to the poor, financial support for orphans, providing loans to the poor, awareness, training vulnerable groups Maclure, R. [ 49 ] Burkina Faso, 1995/ LI Case study Interview *** Two NGOs providing first-aid clinics, maternities, and midwife lodgings for providing services for maternal health and child survival Manna, A. [ 50 ] India, 2019/ LMI Qualitative study Interview ** Using cell phones to communicate with cancer patients Mehta, P. [ 51 ] India, 2013/ LMI Cross-sectional Questionnaire *** Providing medical services for children with cancers Momoh, G. T. [ 52 ] Nigeria, 2015/ LMI Quasi experimental Semi-structured questionnaire/ in-depth interview ***** Strengthen the capacity of 12 NGOs in the field of support and policy related to the emphasis on reproductive health issues Mugisha F [ 53 ] Uganda, 2005/ LI Qualitative study Semi-structured individual interviews ***** Providing reproductive health services Mukherjee S [ 54 ] India, 2017/ LMI Descriptive study Case Studies, semi-structured interviews and unstructured observation/ literature review ***** Providing community participation Nguyen, N. [ 55 ] Low- and middle-income countries, 2014 Online survey …”
Section: Resultsmentioning
confidence: 99%
“…A. [ 47 ] * * * * Khodayari-Zarnaq, R. [ 48 ] * * * * * * Maclure, R. [ 49 ] * * * * Manna, A. [ 50 ] * * * * Mehta, P. [ 51 ] * * * * Momoh, G. T. [ 52 ] * * * * Mugisha F [ 53 ] * * Mukherjee S [ 54 ] * * Nguyen, N. [ 55 ] * * Perry, H. [ 56 ] * * * …”
Section: Resultsmentioning
confidence: 99%
“…Offenbacker divided the barriers to effective public participation into perceptual, political, and supportive [14]. Khodayari et al reported that the main barriers to NGOs' participation in health sector policies are the government and how NGOs operate [15]. The laws of different countries have restrictions and possibilities for people's participation in legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Aghaii pointed to the issue of legal restrictions and noted that only in a minimal number of laws and regulations, the institution responsible for enacting regulations is required or is free to consult with other institutions [20]. Khodayari et al also concluded that legal support and supportive laws could help realize NGOs' potential in legislation [15].…”
Section: Discussionmentioning
confidence: 99%
“…The governments worldwide, particularly in developing nations, have considered NGOs the most appropriate way to achieve maximum population coverage for health care services. Accordingly, such organizations can perform innovative activities, attract public participation, especially in the disadvantaged and rural communities, and empower populations (who live in weakest strata of society) by helping them to improve their quality of life [4][5][6]. Studies have thus far revealed that NGOs' duties in the health sector are not the same in each country, and it depends on some specific characteristics of each region, including levels of development, institutional framework, cultures and traditions, resources, and other needs.…”
Section: Introductionmentioning
confidence: 99%